A New Definition of Fractional Derivatives With Mittag-Leffler Kernel of Two Parameters - Chinchole, Sanjay Madhukar; Bhadane, Ashok (Communications in Mathematics and Applications, 2022)
In this paper, a new fractional derivative with Mittag-Leffler kernel of two parameters is proposed. Several functional properties of this derivative are explained and applied to solve the fractional time Fourier’s law equation.